ISOLASI DAN IDENTIFIKASI Streptomyces sp. PADA KOLAM TANAH DI DESA TENGGUR TULUNGAGUNG JAWA TIMUR - Didik Prasetya (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Tenggur Village, Rejotangan District, Tulungagung Regency is a village where the majority of its residents work as fish farmers. Currently, one of the diseases that attack fish is thought to be caused by infection with Aeromonas hydrophila bacteria, the fish's body parts will bleed, especially the chest, abdomen and at the base of the fins, and the fish will die even though the pond is well maintained. Fish disease control is currently still using chemicals so that the impact of beneficial bacteria will be destroyed in the pond environment and residues of compounds in fish that will be harmful to health if consumed. Streptomyces bacteria are bacteria that are able to produce enzymes and antibiotics that can be used as biocontrol agents for several diseases caused by bacteria. The purpose of this study was to isolate and identify Streptomyces bacteria from soil ponds in Tenggur Tulungagung Village, East Java. Isolation was carried out using the serial dilution method. Streptomyces were isolated from an earthen pond with a depth of 15 cm from the soil surface and planted on Yeast Extract Malt Agar (ISP4) media. The growing colonies were observed macroscopically and microscopically, as well as biochemical tests using the Guide to the Classification and Identification of the Actinomycetes and Their antibiotics from Lechevalier and Waksman (1973). The results showed 4 isolates of Streptomyces sp.1, Streptomyces sp.2, Streptomyces sp.3, Streptomyces sp.4. The four isolates will later be tested against Aeromonas hydrophyla bacteria, which is the cause of Motile Aeromonas septicemia.